2018
DOI: 10.1038/s41598-018-27274-8
|View full text |Cite
|
Sign up to set email alerts
|

NtLTP4, a lipid transfer protein that enhances salt and drought stresses tolerance in Nicotiana tabacum

Abstract: Lipid transfer proteins (LTPs), a class of small, ubiquitous proteins, play critical roles in various environmental stresses. However, their precise biological functions remain unknown. Here we isolated an extracellular matrix-localised LTP, NtLTP4, from Nicotiana tabacum. The overexpression of NtLTP4 in N. tabacum enhanced resistance to salt and drought stresses. Upon exposure to high salinity, NtLTP4-overexpressing lines (OE lines) accumulated low Na+ levels. Salt-responsive genes, including Na+/H+ exchanger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 56 publications
1
42
0
Order By: Relevance
“…The Casparian strips in the roots play an important role in preventing the non-selective apoplastic bypass of salts into the stele, thereby decreasing the accumulation of toxic ions under salt stress [32]. Na + accumulation was lower in tobacco lines overexpressing NtLTP4 when compared with those of wild type lines after salt treatment [33]. Our data suggest that salt-induced increase in the levels of LTP contribute to a greater deposition of suberin in the Casparian bands, bringing about increased salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The Casparian strips in the roots play an important role in preventing the non-selective apoplastic bypass of salts into the stele, thereby decreasing the accumulation of toxic ions under salt stress [32]. Na + accumulation was lower in tobacco lines overexpressing NtLTP4 when compared with those of wild type lines after salt treatment [33]. Our data suggest that salt-induced increase in the levels of LTP contribute to a greater deposition of suberin in the Casparian bands, bringing about increased salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Redundant dye solution was washed away with boiled ethanol, and the leaves were imaged. ImageJ software was used for quantitative analysis of H 2 O 2 and O 2 − intensity [80].…”
Section: Histochemical Staining Of Reactive Oxygen Speciesmentioning
confidence: 99%
“…Further analysis revealed that the SNO-proteins identified were localized to the chloroplast, cytoplasm, cell wall, or vacuole with the majority showing localization to the chloroplast and having diverse functions in photosynthetic electron transfer and carbon utilization. In addition, several, including bifunctional inhibitor/lipid-transfer protein/seed storage 2S albumi, glutathione S-transferase, mannose-binding lectin protein, chlorophyll B-binding protein, and Beta-carbonic anhydrase, have been implicated in stomatal movement in response to stress [43][44][45][46][47]. This suggests that these proteins have important roles in stomatal function that may be regulated via S-nitrosylation.…”
Section: Guard Cell S-nitroso-proteomic Changes In Response To Flg22 mentioning
confidence: 99%